Pengaruh Teman Sebaya Terhadap Kemampuan Kognitif Siswa Berkesulitan Belajar Pada Pembelajaran IPA - Margaretha Ordo Servitri (Prodi PGSD FIP UNM, 2017)
Background of this study was that every learning proces in class commonly found children who had difficulties in learning. The form of difficuties of every student were different, while the learning which were commonly conducted by the teachers in schools still using speech method and excercises only individually so that this cause the learning process only focused on teacher and made the students got difficulties in learning being under-developed in comprehending material of study.This matter could cause the student’s afektive skill getting difficulties in learning became low. Through groups of the peer group, those children would be be more motivated to study so that they could solve their learning disability. This study aimed to clarify the influence of the peer group the student’s afektive skill who got learning disability in Science (IPA) learning.This study used quantitative research metodology with the type of descriptive research method. The data analysis result showed tcount (4.540 ) > ttabel (2.086) that can be taken that Ho decision was refused. So it can be concluded that the peer group has positive effect toward the student’s afektive skills who had learning disability.Keyword: peer group, Science learning, student’s afektive skill with learning disability